Use of marrow multipotent mesenchymal (stromal) cells in renal transplantation - M. Sh. Khubutia; N. V. Borovkova; O. N. Rzhevskaya; A. V. Pinchuk; D. A. Vasilchenkov (Лечащий Врач)
Despite the achievements of immunosuppressive therapy in patients after renal transplantation, duration of graft survival remains unchanged during last few decades. Marrow multipotent mesenchymal (stromal) stem cells (BM MMSC) is a potential tool to influence this situation. Actual experience and gaps in BM MSC data have been analyzed in current publication.